2012
DOI: 10.1111/j.1365-2893.2012.01589.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized controlled trial of dual‐plasmid HBV DNA vaccine mediated by in vivo electroporation in chronic hepatitis B patients under lamivudine chemotherapy

Abstract: A DNA vaccine against the hepatitis B virus (HBV), enhanced by IL-2/IFN-γ fusion protein expression from a plasmid construct and mediated by in vivo electroporation, was evaluated in a total of 39 HBeAg-positive patients with chronic hepatitis B (CHB). The six of 39 patients with a serum alanine aminotransferase (ALT) value of 1-2 times upper limit of normal (ULN) were assigned to the open-label arm (Group01) receiving vaccine monotherapy; the remaining 33 patients with an ALT of more than two times ULN were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 29 publications
3
40
2
1
Order By: Relevance
“…They can be produced by stimulation with PRR agonist, and TLR8 agonist has been shown to be very potent in this respect in the liver 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 17 (Jo et al, 2014). Recombinant forms of these cytokines have not yet been widely used, but several trials performed in animal model or in human, and aiming at investigating DNA vaccination as therapeutic approach have used co-injection of vectors encoding these chemokines, and shown that they indeed improved immune responses (Brass et al, 2015;Chow et al, 1998;Saade et al, 2013;Yang et al, 2012).…”
Section: Chemokines As Adjuvant?mentioning
confidence: 96%
“…They can be produced by stimulation with PRR agonist, and TLR8 agonist has been shown to be very potent in this respect in the liver 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 17 (Jo et al, 2014). Recombinant forms of these cytokines have not yet been widely used, but several trials performed in animal model or in human, and aiming at investigating DNA vaccination as therapeutic approach have used co-injection of vectors encoding these chemokines, and shown that they indeed improved immune responses (Brass et al, 2015;Chow et al, 1998;Saade et al, 2013;Yang et al, 2012).…”
Section: Chemokines As Adjuvant?mentioning
confidence: 96%
“…Female BALB/c mice (6 to 8 weeks old, SPF level) were randomly separated into 13 groups and immunized with each plasmids using in vivo electroporation according to a previously described protocol [22,23,30]. All plasmids were prepared using endotoxin-free purification columns (Omega Bio-Tek, Norcross, GA, USA).…”
Section: Mouse Immunizationmentioning
confidence: 99%
“…In conclusion, the trial suggested that the dual-plasmid vaccine was safe and immunologically effective, and the combination of DNA vaccine and LAM achieved a significant higher positive T-cell response rate (P D 0.03) and a lower virological breakthrough (VBT) rate (P D 0.03) than LAM monotherapy in CHB patients. 69 However, in the following phase IIb trial, the dual-plasmid vaccine failed to achieve significant efficacy in drug resistance and viral breakthrough.…”
Section: Dna-based Vaccinesmentioning
confidence: 99%